High-temperature oxidation evaluation using crystal microbalance. (3rd July 2020) - Nicoli, Michael; Grosjean, Francois; Mingant, Remy; Kittel, Jean; Trueba, Monica; Trasatti, Stefano; Perrot, Hubert; Ropital, Francois
ABSTRACT: High-temperature oxidising environments are frequently encountered but the limited number of in situ techniques that can be implemented has hindered the monitoring possibilities and a better comprehension of the oxidation phenomenon. In this paper, the high-temperature oxidation behaviours of three alloys (AISI 316L, AISI 310 and HAYNES ® HR-120 ® ) were studied by using crystal microbalances. Two types of crystal were tested: quartz or gallium orthophosphate crystals. First the behaviour of thin sputtered deposited alloys on quartz slides was studied at 400 and 700°C under air oxidising conditions and compared to bulk samples. Kinetics measurements were performed on the three alloy films deposited on the resonators at 400 or 700°C: it was possible to measure very small mass variations associated with thin oxide formation between 5 and 180 nm of thickness. The crystal microbalance technique gives promising perspectives in understanding the high-temperature corrosion and scaling mechanisms and also for in situ monitoring.